The impact of oral appliance therapy with moderate mandibular advancement on obstructive sleep apnea and upper airway volume - Pahkala, Riitta; Seppä, J.; Myllykangas, R.; Tervaniemi, J.; Vartiainen, V. M.; Suominen, A. L.; Muraja-Murro, A. (Sleep & breathing, 2020)
Purpose To find out if a moderate protrusion with a mandibular advancement device (MAD) can significantly increase the upper airway volume and, further, what signs and symptoms of obstructive sleep apnea (OSA) can be improved by this maneuver. Methods There were 58 adults diagnosed with OSA who were referred for MAD therapy. The mean apnea-hypopnea index (AHI) was 19.2 (SD 8.6). Five indicators of signs and symptoms of OSA (AHI, oxygen saturation, snoring, daytime sleepiness, and health-related quality of life) were evaluated at the baseline and after 6 months of MAD therapy. Nasal resistance and airway volume and cross-sectional areas with and without the MAD in situ were recorded. Based on AHI reduction, the treatment response was classified as complete, partial, or non-complete. Statistical analyses included the chi-square, t tests, Mann–Whitney U tests, and regression analyses (linear and logistic). Results Twenty-three patients attained a complete response (residual AHI < 5 events/h) to MAD therapy. In 13 subjects, the response was partial, and in 9 patients, it was non-complete. The complete responders were significantly younger, and they had a deeper overbite than partial/non-complete responders. A convex profile associated positively, but a vertically restricted throat and increased lower facial height associated negatively with the increase in airway volume. Conclusions Excellent MAD therapy outcomes were achieved in most patients. Only age and deep bite had some influence on AHI reduction, indicating multifactorial nature in the response to MAD therapy.